THE MAIN TASKS AND FUNCTIONS OF INTERNAL AFFAIRS PREVENTIVE INSPECTORS IN MAINTAINING AND ENSURING THE SAFETY OF PUBLIC ORDER (Scientific journal of the Fergana State University, 2024)
In this article, an unprecedented large-scale reform of the Republic in terms of content and essence in improving the system of internal affairs bodies during the years of independence, the formation of a system that ensures the reliable protection of citizens and society from terrorist, subversive attacks, extremism of all forms, criminal manifestations such as organized crime,, what are the main tasks and functions of preventive inspectors in maintaining public order and ensuring the safety of citizens in making it a reliable guarantee of protection of Public Order and security.